2014
DOI: 10.3855/jidc.4020
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo hemorrhagic fever and its relationship with climate factors in southeast Iran: a 13-year experience

Abstract: Introduction: Crimean-Congo hemorrhagic fever (CCHF) is endemic in southeast Iran. In this study we present the epidemiological features of CCHF and its relationship with climate factors in over a 13-year span. Methodology: Surveillance system data of CCHF from 2000 to 2012 were obtained from the Province Health Centre of Zahedan University of Medical Sciences in southeast Iran. The climate data were obtained from the climate organization. The seasonal auto-regression integrated moving average (SARIMA) model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 27 publications
2
45
0
4
Order By: Relevance
“…Some of the seasonal and climatic covariates were previously reported as important predictors of CCHF virus infections [3e5]. Areas with higher temperatures, precipitation and humidity were linked with high CCHF occurrence in Bulgaria and Iran [4,5]. Suitable habitat for H. marginatum ticks was reported as fragmented agricultural lands, forested lands and grass cover in Turkey and Bulgaria, and non-irrigated agricultural land (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the seasonal and climatic covariates were previously reported as important predictors of CCHF virus infections [3e5]. Areas with higher temperatures, precipitation and humidity were linked with high CCHF occurrence in Bulgaria and Iran [4,5]. Suitable habitat for H. marginatum ticks was reported as fragmented agricultural lands, forested lands and grass cover in Turkey and Bulgaria, and non-irrigated agricultural land (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several statistical models including Seasonal Autoregressive Integrated Moving Average (SARIMA) have been employed to predict infectious diseases such as tuberculosis , dengue , malaria , influenza , Crimean‐Congo hemorrhagic fever and ZCL . Climatic variables are considered important external factors in the prediction models of some vector‐borne diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated the presence of different species of the flea, lice, mite and tick infestation in rodents. Other studies have been shown that ectoparasites associated with rodents could be responsible for distribution of the important zoonotic diseases such as CrimeanCongo Hemorrhagic fever (CCHF) and plague [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The Jaz murian region in the southeast of Iran situated in the tropical realm and is considered as an endemic area of malaria and CCHF in Iran [8,10]. Due to the diverse climatic and geographical conditions in the Jaz Murian area, the identification of the fauna of ectoparasites in wild rodents could be helpful to control zoonotic arthropod-borne diseases.…”
Section: Introductionmentioning
confidence: 99%